Long-Term Behavior of Self-Compacting Concrete Incorporating Palm Oil Fuel Ash and Eggshell Powder as Partial Cement Replacement - Muhammad Zarif Syahmi; Goh, Wan Inn (Recent Trends in Civil Engineering and Built Environment, 2021)
Self-compacting concrete (SCC), is an innovative concrete that uses less aggregates, but high content of cement compared to normal concrete. It is able to flow by itself and does not require compaction. Therefore, the consumption of cement is higher in producing a good quality and strength of SCC. To minimize the usage of the cement in the SCC, Palm Oil Fuel Ash (POFA) and Eggshell Powder (ESP) were used as partial cement replacement materials for an alternative solution. This experimental work was conducted to study the mechanical behaviour of SCC incorporating POFA and ESP as cement replacement. The cement was partially replaced with 5% of POFA and 2.5% of ESP. A total of 18 cubes and 6 cylinders were prepared for determining compressive and tensile strength of SCC respectively, while 6 cylinders were additionally prepared to determine modulus of elasticity. The specimen of cubes were cast in dimensions 100 mm x 100 mm x 100 mm for compressive test at the ages 7, 28 and 56 days. Meanwhile, cylinders were cast in diameter 100 mm with height 200 mm for tensile test and modulus of elasticity, at the age 28 days. The workability of the fresh concrete also were determined by using tests such as slump flow, J-ring and segregation tests. It has been verified that SCC with addition of POFA and ESP had better workability compare to conventional SCC. Furthermore, based on the results, it was observed that the combined of POFA and ESP as cement replacement in SCC had good effect on the compressive and tensile strength. It was found that 5% POFA and 2.5% ESP in SCC had maximum compressive and tensile strength of 4.01% and 6.85% higher than conventional SCC achieved. From the results, it show the mixture of 5% POFA and 2.5% ESP in SCC had greater performance and more environmental friendly than conventional SCC.